The best short plays, 1983 - Delgado, Ramon (Radnor, PA : Chilton, 1983)
A need for Brussels sprouts / Murray Schisgal -- Andante un poco mosso / Jennifer Johnston -- Old soldiers / Martin Jones (etc.).
Young Adult
Keywords: Drama -- Collections; One-act plays -- Collections; Drama -- Collections; One act plays -- Collections